SOSIOLOGI LEMBAGA PENDIDIKAN ALIYAH: STUDI TENTANG TANGGUNG JAWAB PEMERINTAH, MASYARAKAT, DAN KELUARGA DALAM MENEJEMEN AKSES PENDIDIKAN ANAK MARJINAL - Novita Dwi Nur Hidayati; Muhammad Hanif (PT. Saha Kreasi Indonesia, 2026)
This study aims to sociologically examine the roles and responsibilities of the government, community, and family in ensuring access to education for marginalized children at Madrasah Aliyah institutions. The research is grounded in the persistently low Net Enrollment Rate (NER) at the senior secondary level, which nationally stands at only 61.65 percent (BPS, 2023), with children from marginalized groups being the most vulnerable to dropping out of school. The study employs a qualitative approach using a case study method, with data collected through in-depth interviews with the Vice Principal of Student Affairs, the Vice Principal of Facilities and Infrastructure, the Vice Principal of Public Relations, and classroom teachers. The findings reveal four primary forms of support for marginalized students: (1) Guidance and Counseling (BK) services that specifically accompany students facing economic and social disadvantages; (2) active involvement of alumni associations in periodic motivational activities; (3) multilayered access to financial assistance through KIP (Smart Indonesia Card), UP2 (Education Program Management Unit), and fee reductions from the pesantren institution; and (4) direct financial assistance from the foundation chairman to boarding students experiencing economic hardship. The discussion is framed using Bourdieu's theory of social reproduction, Putnam's social capital theory, and Bronfenbrenner's ecological development model. The study concludes that pesantren-based Madrasah Aliyah has significant potential as an effective model of inclusive education through multi-stakeholder synergy among institutions, government, communities, and foundations, bound together by Islamic values and a commitment to serving the underprivileged.